(untitled) (International Journal of Engineering and Computer Science, 2016)
Wireless communication networks became ubiquitous. Mobile ad hoc networks (MANETs) have become an exactly right option that can be chosen for on-demand infrastructure less communications. Besides the enhancements in Mobile ad hoc networks (MANETs) communications, more research can be done on these networks, if they have to be used for video streaming. The reason behind this is that, the Mobile ad hoc networks (MANETs) devices are resource constrained and thus efficient methods to support multimedia communications supporting video streaming is a defiance problem. This is because videos are delay sensitive and thus good quality streaming is inevitable. In the proposed work we use AODV protocol and an idea of Dynamic congestion detection and routing. In this work we define Signal to noise ratio threshold at nodes in all the previously visited paths from source to destination in order to identify the congestion level at the nodes dynamically and construct an optimal path for the transmission of video packets in Mobile ad hoc networks (MANETs) . This decreases the traffic which occurs due to multiple feedback messages from nodes in the network. Hence this approach decreases the loss of packets and this leads to the improvement in the performance.